Designs and Applications of Circularly Polarized Thermally Activated Delayed Fluorescence Molecules. (3rd March 2021) - Frédéric, Lucas; Desmarchelier, Alaric; Favereau, Ludovic; Pieters, Grégory
Abstract: The design of fluorophores merging circularly polarized luminescence and thermally activated delayed fluorescence properties has recently emerged as a promising direction for the development of efficient CP‐Organic Light‐Emitting Diodes (CP‐OLEDs). This progress report gives an overview of the molecular designs explored to obtain CP‐TADF properties, of their performances as chiral emitters in CP‐OLEDs, and discusses future challenges for this burgeoning field of research. Abstract : This progress report gives an overview of the molecular designs explored so far to merge circularly polarized luminescence and thermally activated delayed fluorescence properties, discusses the application of such molecules to construct circularly polarized‐organic light‐emitting diodes and future challenges for this burgeoning field of research.